New Titanosauria (Dinosauria, Sauropoda) remains from the Upper Cretaceous (Plottier Fm) of the southern Neuquén Basin (Patagonia, Argentina) - Bellardini, Flavio; Baiano, Mattia Antonio; Barrios, Francisco; Holgado Palacios, Borja; Coria, Rodolfo Anibal (Journal of Iberian Geology)
Purpose: New sauropod remains (MCF-PVPH-889, MCF-PVPH-899, and MCF-PVPH-900) collected from the Plottier Fm (Coniacian–Santonian) in the south-west of the Neuquén Basin, are here reported. The materials proceed from a fluvial outcrop composed by siltstone and fine sandstone, whose fossil record is known for large-sized sauropod taxa. Methods: Due to the fragmentary condition of the dorsal ribs and the tibia, we focus the description mainly on the femur and the fibula. Results: The specimen MCF-PVPH-889 consists of partially associated postcranial elements represented by a left femur and three fragmentary dorsal ribs of a Titanosauria indet. A right fibula (MCF-PVPH-900) represents another titanosaurian element, while a proximal portion of a right tibia (MCF-PVPH-899) of a smaller individual than others is here referred to as a Sauropoda indet. MCF-PVPH-889 and MCF-PVPH-900 share some features with other titanosaurian taxa (e.g., a femur with medial deflection of the proximal end and elliptical mid-shaft cross-section, a fibula with slightly sigmoidal shaft and well-developed lateral tuberosity) like in Epachthosaurus and Antarctosaurus. However, the femur, with a poorly developed lateral bulge and a relatively low head, and a fibula, with a slender and nearly straight proximal third of the shaft, represent plesiomorphic conditions among titanosaurians. Conclusions: The new remains represent a new sauropod record from the Plottier Fm (Upper Cretaceous). Nevertheless, due to the lack of more diagnostic elements, we prefer to consider the specimens MCF-PVPH-889 and MCF-PVPH-900 as Titanosauria indet, and the MCF-PVPH-899 as Sauropoda indet. This new evidence expands the Coniacian sauropod record of the Neuquén Basin and contributes, in some measure, to our knowledge of the stratigraphical distribution of sauropods from the Patagonian Upper Cretaceous fossil-bearing levels. Fil: Bellardini, Flavio. Provincia del Neuquén. Municipalidad de Plaza Huincul. Museo "Carmen Funes"; Argentina. Dirección Provincial de ...